The industrial expansion and the modern urbanism (2003)
The investigation studied the process of industrial expansion of Bogota towards the west during the first half of the XX century. In this text the existing city-planning relation between industrial implantation and urban growth is analyzed, studying the contributions or the deficiencies of the discipline of urbanism to explain and to guide the phenomenon in the city of Bogota.